ASSESSMENT OF THE NON-LINEAR PERFORMANCE OF STEEL HIGH-RISE BUILDINGS (Nigerian Journal of Technology, 2018)
The study carried out an assessment of the non-linear performance of high-rise buildings in Nigeria and countries of similar earth-tremor records. Symmetric, regular Steel Dual-Concentric (chevron) Braced Frames (SD-CBF) building model was idealized, and its elastic design and non-linear-static analysis were executed using SAP2000 v15 to determine the response of the building to the highest magnitude of` earth tremor ever experienced in Nigeria which was about 4.8 on the moment magnitude scale. From the assessment, it was inferred that, the buildings will perform well for the purpose it was designed, as the onset of inelastic weakening or instability of the building can easily be detected from the plastic response of the braces and so easily retrofitted with consequent savings in human lives and economy. It was established that the buildings will do well on all soil types specified by EC8 (2004) and increase in the Peak Ground Acceleration which is an indicator of the seismic hazard, increases the global displacement of the buildings. Keywords: Earth-tremor, SD-CBF, Finite Element, Peak Ground Acceleration and Seismic Hazard.